Vertebral collapse and polymethylmethacrylate breakage after vertebroplasty: A case report. Issue 34 (August 2019) - Huang, Anquan; Fang, Shenyun; Wang, Liyu; Xu, Renjie; Shen, Jun; Zhu, Guoqing; Miao, Ye; Zou, Tianming
Abstract: Rationale: Vertebral augmentation has become the main treatment for osteoporotic vertebral fractures (VFs). In this article, we report a very rare case of vertebral collapse and polymethylmethacrylate (PMMA) breakage after vertebroplasty. We describe the clinical characteristics and revision surgery performed to remove the broken PMMA cement, maintain stability, and corrects the kyphotic deformity, and we analyze the possible causes. Patient concerns: A 72-year-old man who suffered back pain underwent first lumbar vertebra (L1) percutaneous vertebroplasty (PVP) due to osteoporosis and a vertebral fracture in May 2013. Postoperatively, the patient's back pain was markedly alleviated. Unfortunately, his lumbar back pain recurred in November 2015. Diagnoses: Plain radiographs showed collapse of the L1 vertebral body, breakage of the PMMA cement, and severe kyphosis at the thoracolumbar junction. Interventions: The posterior pedicle was internally fixed and an anterior artificial vertebral body implant was placed to maintain stability and correct the kyphotic deformity in a 2-step surgical procedure. Outcomes: The back pain was alleviated and the patient returned to daily life for more than two years. Lessons: This case demonstrates that PVP is not a simple minimally invasive surgery, and significant postsurgical care is necessary. The true cause of this rare phenomenon remains unclear, but the long-term use of steroids, new injuries, and poorly corrected kyphosis after PVP may play a role. Surgeons must be aware of the kinds of complications that may occur, including rare complications such as vertebral lysis.